2005
DOI: 10.1889/1.2036455
|View full text |Cite
|
Sign up to set email alerts
|

P-33: Identification of Simulated Targets as a Function of Target and Background Blur

Abstract: Simulated imagery was used to determine the effect of target and background blur on target identification performance.An interaction between these two variables was found, indicating that greater image detail may not improve performance, and hence may not be required in applications for which high-resolution databases are not readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Previous work [5] has shown that target contrast, as opposed to the detail of surrounding terrain, is the main determinant of target identification performance in the present experimental context. Therefore, a single background image was used.…”
Section: Stimuli and Apparatusmentioning
confidence: 62%
“…Previous work [5] has shown that target contrast, as opposed to the detail of surrounding terrain, is the main determinant of target identification performance in the present experimental context. Therefore, a single background image was used.…”
Section: Stimuli and Apparatusmentioning
confidence: 62%
“…The target identification data were obtained from Geri et al [3]. Their test stimuli consisted of a right-or left-facing M1-tank model superimposed on a background image obtained from a standard flight simulator database.…”
Section: Psychophysical Identification Datamentioning
confidence: 99%
“…The analysis presented here is part of a research project whose goal is to characterize the effect of target and background detail on target identification performance when performing air-toground tasks in flight simulators. Recent studies in our lab examined the effect of target and background blur on left vs. right target identification performance using imagery similar to that seen in targeting pods [3]. Various models have been proposed for characterizing target identification performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown (Geri, et al, 2005) that a decrease in background blur, defined by the Fourier spectra of the background imagery, results in a decrease in performance in an air-to-ground target identification task. In Experiment 1, we have assessed target identification for various levels of database resolution and slant range (viewing distance).…”
Section: Introductionmentioning
confidence: 99%